Drip Fertigation Technology for Enhancing Water and Nutrient Use Efficiency in Arid Agro-ecosystem of Irrigated North-Western Rajasthan - Yadav, B S; S Chauhan, R P (Annals of Arid Zone, 2017)
Field experiments were conducted from 2002 to 2012 in AICRP on IWM at Agricultural Research Station, Sriganganagar to find out optimum crop geometry under drip system, optimum drip irrigation schedule and optimum fertigation schedule for American cotton (hybrid hirsutum cotton), Bt cotton, sugarcane and brinjal. The pooled results of the trials revealed that paired planting in Bt cotton, sugarcane and brinjal was found cost effective without any yield loss. In American cotton paired planting gave significantly higher seed cotton yield over single row planting. Drip irrigation schedule at 1.0 ETc, 1.0 ETc, 80% PE and 1.0 ETc was found optimum for American cotton, Bt cotton, sugarcane and brinjal, respectively. The increase in yield of respective crops was 24.2, 31.0, 26.4 and 30.9% and saving of water was 13.3, 32.9, 17.1 and 29.6% over conventional practice. Drip irrigation also improved the quality of produce by increasing fibre length and fineness in cotton lint and commercial cane sugar to the extent of 35.8% over conventional practice. Drip irrigation also suppressed the pest population in cotton. The fertigation schedule 150 kg N and 20 kg K2O ha-1 (40 kg P2O5 ha-1 as basal) in 6 equal splits at an interval of 15 days for American cotton, 120 kg N, 32 kg P2O5 and 16 kg K2O ha-1 in 6 equal splits at an interval of 15 days and 2% foliar spray of KNO3 at 90 and 105 days after sowing for Bt cotton, 112.5 kg N and 30 K2O ha-1 (40 kg P2O5 ha-1 as basal) in 9 equal splits at an interval of 20 days for sugarcane and 96 kg N and 48 K2O ha-1 (80 kg P2O5 ha-1 as basal) in 12 equal splits at an interval of 10 days for brinjal was found optimum. The increase in yield of respective crops due to optimum fertigation schedule was 49.8, 15.6, 20.7 and 30.6% and water saving was 13.3, 24.3, 25.0 and 29.6% and fertilizer saving was 0, 20, 25 and 20% over conventional practice of irrigation and fertilizer application. In both drip irrigation and fertigation water expense efficiency increased by 43.3 to 85.9% over that of conventional practice. Thus, drip irrigation with fertigation was found a better option to increase water and nutrient use efficiency in arid agro-ecosystem of Irrigated North Western Rajasthan.